Ethnobotanical Study on Traditional Cuisine of the Jakun Community in Kampung Peta, Johor Malaysia - Sham, Salmysha Naziera; Sabran, Siti Fatimah (Enhanced Knowledge in Sciences and Technology, 2025)
This ethnobotanical study explores the traditional cuisine of the Jakun community in Kampung Peta, Johor, focusing on the plants used, cooking methods, and cultural practices. The study aims to document and analyze the traditional knowledge of the Jakun community, emphasizing the role of plants in their daily lives and cuisine. Data were collected through semi-structured interviews with three experienced informants and participatory observation. A total of 11 plant species were identified, including cassava (Manihot esculenta), torch ginger (Etlingera elatior), and pitcher plants (Nepenthes mirabilis), and eight other species serving distinct culinary roles. The findings reveal the diverse uses of these plants, such as cassava as a staple ingredient, pitcher plants as natural food vessels, and Phrynium leaves as wrappers for steaming food. The preparation of signature dishes like Nasik Randau a communal rice dish wrapped in Phrynium leaves, and Keket Daging, a traditional meat dish cooked with local spices, highlights the community’s reliance on locally sourced plants and traditional methods. The cultural significance of these culinary practices underscores the Jakun community’s connection to their natural environment and their efforts to preserve heritage through foods. However, modernization has introduced changes, with modern tools largely replacing traditional utensils, although some conventional practices persist. This study concludes that the Jakun community’s culinary traditions are deeply rooted in their environment and cultural heritage. It emphasizes the importance of documenting and preserving traditional knowledge to maintain cultural identity and sustainable practices in the face of modernization.